Are we restoring enough? Simulating impacts of restoration efforts on the suitability of forest landscapes for a locally critically endangered umbrella species. Issue 4 (9th November 2017) - Hof, Anouschka R.; Hjältén, Joakim
Abstract : Habitat restoration is often implemented to mitigate the negative effects of intensive forestry on biodiversity. It may be increasingly adopted in future to alleviate additional negative effects of climate change. Ascertaining the restoration effort needed to fulfill project goals is difficult. Insights may be gained through simulating the effects of restoration efforts on landscape dynamics through time. Here we used a spatially explicit landscape simulation model to simulate the effects of different restoration efforts on forest landscapes in Sweden to assess the level of mitigation that is needed to allow viable populations of the locally critically endangered White‐backed Woodpecker ( Dendrocopos leucotos ); an umbrella species whose protection may serve the protection of a range of other species. Based on the goals of the protection plan for the species, which reflect its habitat requirements, we evaluated which of several restoration scenarios could fulfill goals with respect to (1) the amount of deciduous forest; (2) the amount of dead wood; and (3) the age of the forest. We found that whereas it may be relatively easy and quick to acquire high levels of dead wood, increasing the proportions of deciduous forest and of old forests require considerably more time and effort. Also, current management actions would not be sufficient to create the required amount of habitat to conserve the White‐backed Woodpecker in our study region. Simulations like ours can provide valuable information about the levels of restoration needed through time to fulfill project goals and may prevent wasting valuable resources, time, effort, and money.